An overview of resilience in the children of the Mahadul Yatama Islamic Boarding School students - Febriantie, Eka Ladya Charyl; Amelasasih, Prianggi (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2025)
Islamic boarding schools (pesantren) in Indonesia provide a unique, collective living environment that shapes student character. For orphaned students, such as those at Pondok Mahadul Yatama, this setting presents compounded challenges, requiring them to navigate the loss of parental support while adapting to a highly structured and disciplined lifestyle. This context creates significant emotional, social, and psychological pressures that necessitate a high degree of resilience. This study aims to provide an in-depth description and understanding of the lived experiences of resilience among orphaned male santri as they adapt to life at the Mahadul Yatama Pesantren. A qualitative research design with a phenomenological approach was employed. The subjects were male santri aged 12-18 who had resided at the pesantren for 2-6 months. Data were collected through in-depth, semi-structured interviews and non-participant observation. The collected data were then analyzed using a thematic analysis approach to identify recurring patterns and themes. The findings indicate that resilience among the santri is a dynamic process. Key themes emerged, including the development of personal competence through overcoming initial adaptation difficulties, a positive acceptance of change driven by peer support, and the crucial role of spiritual influences. Prayer and faith were consistently identified as primary coping mechanisms for managing feelings of homesickness and stress, serving as a significant source of inner strength.